Apparatus for recycling and treating plastic foam - WANG XIAOHU; ZHANG WEILONG; ZHOU JINQIANG (2018)
The invention discloses an apparatus for recycling and treating plastic foam. The apparatus comprises a metal box body, and an inner box is arranged in the metal box; a pressure head which is controlled by a cylinder is arranged over the metal box body, an elevating board controlled by the cylinder is arranged at the bottom of the inner box, foam is placed on the elevating board, the pressure headis used for carrying out rolling of the foam on the elevating board, and a positioning column and a heating pipe are arranged between the metal box body and the inner box; the pressure head which ismatched with the heating pipe is provided for carrying out rolling of the foam, finally a suction pipe and a water draining pipeline are matched for carrying out recovery, in order to improve recoveryefficiency of the foam. 本发明公开了种塑料泡沫的回收处理装置，包括有金属箱体，所述金属箱体中设置有内箱，所述金属箱体的上方设置有气缸控制的压头，所述内箱的底部设置有气缸控制的升降板，将泡沫放置在升降板上，由压头来对升降板上的泡沫进行碾压，所述金属箱体与内箱之间设置有定位柱和加热管；通过设置有压头配合加热管来对泡沫进行碾压，最后由吸管和放水管路配合来进行回收，以提高泡沫的回收效率。